Szylkret, bioorganiczny materiał w rzemiośle artystycznym – zagadnienia z zakresu materiałoznawstwa, technologii i stosowanych technik dekoracyjnych oraz niszczenie - Podgórski, Andrzej; Tomaszewska-Szewczyk, Alina (Acta Universitatis Nicolai Copernici Zabytkoznawstwo i Konserwatorstwo, 2016)
Tortoiseshell was one of the earliest materials which has been used to the ornamental purposes. It is obtained from the outer layer of dermal bone of three species of sea turtles: tortoiseshell, green and loggerhead. Dermal bone is formed by scutes, strongly interconnected with each other, with characteristic layered structure. Chemically has a similar composition to the horn and mainly consists of keratin – hydrophilic, fibrous protein, insoluble in water with good resistance to physical and chemical agents. Dermal bone has a two-phase structure, in which keratin fibers are embedded in the amorphous matrix with a high content of sulfur. Tortoiseshell properties shall be described with accordance by the standards adopted for decorative stone. Carapace was used for making ornaments since antiquity in many cultures. In 1973 introduced global ban on trade of tortoiseshell on the basis of the Convention on International Trade in Endangered Species. Processing of dermal bone based on its forming at high temperature, of around 100°C and cooling to room temperature with a given form. Surfaces of objects made from tortoiseshell were carved, inlay decorated and piqué technique. It was also used in marquetry. The finished product is susceptible to mechanical damage, loses its shine, it darkens, delaminate, and may be biodegradable.